Production of durian seed starch-based bioplastic reinforced with pineapple leaf fiber cellulose - Nawangsari, Putri (BKS-TM Indonesia, 2025)
Petroleum-based plastics are a significant source of pollutants, contributing to environmental problems, human health issues, and potential ecosystem damage. The developed bioplastics from renewable resources offer an alternative material to petroleum-based plastics. This study aims to investigate the feasibility of producing bioplastic from durian seed starch reinforced with cellulose from pineapple leaf fibers. The composition ratio of starch and cellulose is 100:0; 99:1; 98:2, 97:3; 96:4; and 95:5 vol % using glycerol as a plasticizer at 20% (wt/v) of glycerol to starch. Bioplastics were fabricated through the phase inversion method. Durian seed starch solution, cellulose, and glycerol were mixed using a hot plate magnetic stirrer for 30 minutes. The mixtures were poured into a flat mold and were dried in the oven at a temperature of 100 °C for 90 minutes. Analysis of bioplastic includes tensile strength, water absorption, and biodegradation. The tensile test and water absorption test were referred to ASTM 638 14 and ASTM D 570, respectively. The results reveal that an increasing volume fraction of (1-4% vol) cellulose in bioplastic-based durian seed starch enhances the tensile strength and biodegradation. Conversely, it decreases in water absorption. The best results are found in bioplastic with a starch-to-cellulose ratio of 96:4% vol. The bioplastic has a tensile strength of 11.881 MPa, water absorption of 1.361%, and biodegradation of 67.3 in 10 days